PATIENT PERCEPTION OF COMPLIANCE WITH FAMILY DRINKING HYPERTENSION DRUG AND DIET IN THE HEART OF POLY RSD SIDOARJO - Sajidin, Muhammad (JURNAL KEPERAWATAN BINA SEHAT, 2013)
The results from the MONICA (Multinational Monitoring of Trends Of Determination In Cardiovascular Diseases) incidence in Indonesia ranges between 6-18%, so roughly there are 20 million people with hypertension. According to the data at the heart of poly RSD Sidoarjo, patients recorded hiprtensi on as many as 15625 people in 2010 and in 2011 as many as 16 237 people. People assume that severe hypertension is not a disease, they underestimate hypertension. They assume hypertension is not difficult to handle. Perception of how the family is a family give meaning or interpretation of a stimulus. It is the difference in mean menyebahkan suggestions given by health workers for treatment programs for patients with hypertension. A hypertensive patient treatment will be very excited if the support of family members. With the family who can perceive the stimulus correctly, then the patient will be able to undergo treatment well, and increase motivation to adhere to treatment and diet she lived. Support health professionals is another factor that can affect patient adherence to face the fact that the new healthy behaviors is important.Keywords: Perception family, Hypertension